2013
DOI: 10.1038/srep01825
|View full text |Cite
|
Sign up to set email alerts
|

Constant Communities in Complex Networks

Abstract: Identifying community structure is a fundamental problem in network analysis. Most community detection algorithms are based on optimizing a combinatorial parameter, for example modularity. This optimization is generally NP-hard, thus merely changing the vertex order can alter their assignments to the community. However, there has been less study on how vertex ordering influences the results of the community detection algorithms. Here we identify and study the properties of invariant groups of vertices (constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…This can be more specifically measured in terms of number of invariant groups of vertices which stay in the same output community in spite of the fluctuation. These groups have been termed as "constant communities" [25]. In our earlier work, we showed that despite such fluctuations in the final outcome, there exist few such constant communities which always remain same across different vertex orderings.…”
Section: Effect Of Vertex Orderingmentioning
confidence: 94%
“…This can be more specifically measured in terms of number of invariant groups of vertices which stay in the same output community in spite of the fluctuation. These groups have been termed as "constant communities" [25]. In our earlier work, we showed that despite such fluctuations in the final outcome, there exist few such constant communities which always remain same across different vertex orderings.…”
Section: Effect Of Vertex Orderingmentioning
confidence: 94%
“…Recently, Chakraborty et al [5] pointed out how vertex ordering influences the results of the community detection algorithms. They identify invariant groups of vertices (named as "constant communities") whose assignment to communities are not affected by vertex ordering.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the optimal values of the scoring functions do not provide any insight as to whether a network actually possesses community structure or not. For example, the highest modularity in the Jazz network is 0.45 [5] and that of the Western USA power grid is 0.98 [5,13]. However, it has been observed [5,13], that Jazz has a much stronger community structure than the power grid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each c i ∈ C is an induced sub-graph of G. Membership nodes are determined by using 3 NMF which can be defined as; let X be an n × m non-negative matrix then, NMF factorizes X into non-negative matrices W 4 and H , such that [15]; 5 X ≈ WH .…”
mentioning
confidence: 99%